Find the general solution of
(y-xu)p+(x+yu)q=x2+y2
Given, "(y-xu)p+(x+yu)q = x^{2}+y^{2}".
This equation is of the form "Pp+Qq=R" (Lagrange's linear partial differential equation).
Here, "P = y-xu, Q=(x+yu), R = x^{2}+y^{2}".
The subsidiary equations are
"\\dfrac{dx}{P}=\\dfrac{dy}{Q}=\\dfrac{du}{R}\\\\\n\\dfrac{dx}{y+xu}=\\dfrac{dy}{-(x+yu)}=\\dfrac{du}{x^{2}+y^{2}}~~~~~~~~~~~-(1)".
Each ratio of (1) is equal to "\\dfrac{xdx+ydy}{(x^{2}-y^{2})u} = \\dfrac{dx+dy}{(1-u)(y-x)}".
Let us consider,
"\\dfrac{xdx+ydy}{(x^{2}-y^{2})u} = \\dfrac{du}{x^{2}-y^{2}}\\\\\nxdx+ydy=udu\\\\\n\\text{Integrating, }\\\\ \\int xdx + \\int ydy = \\int zdz\\\\\n\\dfrac{x^{2}}{2}+\\dfrac{y^{2}}{2} =\\dfrac{z^{2}}{2}+\\dfrac{c_{1}}{2}\\\\\nx^{2}+y^{2}-u^{2}=c_{1}"
Consider,
"\\dfrac{dx+dy}{(1-u)(y-x)}=\\dfrac{du}{(x+y)(x-y)}\\\\\n\\dfrac{dx+dy}{1-u}=\\dfrac{du}{-(x+y)}\\\\\n-(x+y)d(x+y)=(1-u)du\\\\\n\\text{Integrating,}\\\\\n-\\int (x+y)d(x+y)=\\int (1+z)dz\\\\\n-\\dfrac{(x+y)^2}{2}=\\dfrac{(1-z)^{2}}{-2}+\\dfrac{c_{2}}{2}\\\\\n(1-u)^{2}-(x+y)^{2}=c_{2}"
The general solution is,
"\\phi(c_{1},c_{2})=0\\\\\n\\phi\\left(x^{2}+y^{2}-u^{2}, (1-u)^{2}-(x+y)^{2}\\right)=0."
Comments
Leave a comment